2020
DOI: 10.1186/s12917-020-02366-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs, MRI findings and outcome in dogs with peripheral vestibular disease: a retrospective study

Abstract: Background: Vestibular dysfunction is relatively common in dogs, with a prevalence of 0.08% reported in primary veterinary care in the UK. There are several studies investigating how to differentiate between peripheral and central vestibular disease but only limited information regarding the possible underlying causes for peripheral vestibular dysfunction in dogs. This study therefore aimed to describe the clinical signs, magnetic resonance imaging findings (MRI), underlying causes and outcome in a large popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 31 publications
7
35
0
Order By: Relevance
“…Idiopathic vestibular disease was the most common condition in our study population. Although this is in agreement with previous reports, 9,17 it has also been suggested that otitis media interna should be considered the most common cause of peripheral vestibular disease in dogs. 1,5 Our study included exclusively cases referred to a specialist hospital, which could have favoured emergency presentations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Idiopathic vestibular disease was the most common condition in our study population. Although this is in agreement with previous reports, 9,17 it has also been suggested that otitis media interna should be considered the most common cause of peripheral vestibular disease in dogs. 1,5 Our study included exclusively cases referred to a specialist hospital, which could have favoured emergency presentations.…”
Section: Discussionsupporting
confidence: 93%
“…It is therefore possible that dogs with vestibular signs caused by otitis media interna will also display non‐neurological signs, such as head shaking, ear discharge and pain on opening of the mouth or palpation of the bullae 1 . It should however be noted that otitis media interna is not always caused by extension of otitis externa, and chronic otitis externa will not necessarily result in otitis media and interna 17,41 . This is in agreement with the findings of this study in which only two thirds of dogs with otitis media interna had a clinical history of previously diagnosed otitis externa, and otitis externa was also commonly observed in dogs suffering from other causes of vestibular syndrome (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…36 Similar breeds were mentioned by some recently published studies consistent with our ndings. 2,37 In the present study, the median age at onset of neurological de cits was 115 months (9.58 years). Median age reported recently elsewhere ranged from 6.8 years to 12.68 years.…”
Section: Discussionmentioning
confidence: 49%
“…These signs are the most frequently observed clinical ndings consistent with vestibular syndrome. 2,32,37,41 In summary, although the sample size in this case series was small, the cases included appear to be representative for the commonly affected canine population by vestibular syndrome.…”
Section: Discussionmentioning
confidence: 87%